Enzymatic Production Of Feruloylated Acylglycerols From Olive Fatty Acid Distillates As Sunscreen Agents - Kong, Ching (2008)
This work was instigated to produce a novel sunscreen agent based on ferulate glycerol esters with the incorporation of olive fatty acid distillate, glycerol and ethyl ferulate by enzymatic processes. A suitable HPLC detection method was devised for the quantification of the produced novel ferulate glycerol esters. The best separation was found in the combined analytical parameters of mobile phase of 90:10 (ml/ml) acetone: acetonitrile, with additional 1.2% (ml/ml) of acetic acid, running through a reversed phase C8 column (Purospher® STAR RP-8e 5 μm, Merck, Germany) with detection by a UV detector at 350 nm. The peaks retention time was confirmed at 3.14, 3.27, 3.37, 3.96., 4.14, 6.70, 6.95, 7.44 and 7.88 min for ferulate glycerol, ferulic acid, ethyl ferulate, ferulate monoolein, the unidentified peak A, peak B, peak C, peak D and ferulate diolein, respectively The effects of reaction parameters such as lipase type, reaction temperature, lipase concentration, molecular sieves content, free fatty acid to ethyl ferulate molar ratio and total glycerol to acyl-donor molar ratio on the production of ferulate glycerol ester were studied. The immobilized lipase Novozym® 435 of Candida antarctica was found to be the best performing lipase and it was observed that the reaction parameters of the reaction at 5% (w/w) of Novozym® 435, reaction temperature of 70 ºC, with a total glycerol to fatty acid and ethyl ferulate molar ratio of 1:2:1, in presence of 3% (w/w) molecular sieves had resulted in an optimal yield of 64.19% of ferulate glycerol esters. The resulted ferulate glycerol ester mixture was partially purified through micro-filtration and neutralization process and this had increased the ferulate glycerol esters content to 70.12% (yield). The partially purified ferulate glycerol esters mixture was analyzed through in-vitro analysis for its SPF value, mean critical wavelength and the UVA/UVB protection ratio. The results indicated that the partially purified ferulate glycerol esters mixture at 70.12% (yield) purity provides a protection factor of SPF 10.40 in the UVB region and a moderate protection in the UVA region. A test on 15% (w/w) preparation of the partially purified ferulate glycerol ester confirms that the ferulate glycerol esters mixture is capable of providing a basic protection of SPF 3.94, with good protection in the UVB region and a moderate protection in the UVA region.